Assessment of storage losses and comparison of underground and aboveground storage for better stability and quality of maize (zea mays l.) and sorghum (sorghum bicolor l.) grains in selected districts of jimma zone, Ethiopia. (September 2021) - Muleta, Obsuman D.; Tola, Yetenayet B.; Hofacker, Werner C.
Abstract: Production and marketing of cereal grains is one of main activities in low income countries farming system. However, yields are very low due to several factors associated with traditional practices. Despite low productivity, the postharvest loss (PHL) of grains mainly during storage is high due to storage pests. The study was conducted to assess storage related losses of grains (maize and sorghum) and compare aboveground and underground storage methods to minimize losses associated with traditional storage structures. In first phase of the study, base line data were collected using focus group discussion, key informants interview and semi-structured questioners. In the second phase, underground and aboveground storage methods were investigated along with their control for better stability of stored maize and sorghum. The survey result showed that, storage related losses (due to different factors) of maize and sorghum were 14.2 and 11.5% respectively. The major identified causes of losses were storage pests and losses due to seepage. In the second phase, from studied storage structures, grains stored in pit storage with PVC layer showed superior stability and quality in terms of prevention of pest attacks and proximate composition, respectively. The study demonstrated that, underground storage method supported with PVC lining was efficient in terms of enhancing storage stability of grains with required quality for consumption or marketing. Highlights: Traditional storage structures are ineffective against pests and adverse climates. Poor efficiency results in high storage losses of grains. Insects and moulds are the major causes for quantitative and qualitative losses. Improving the traditional practice reduced losses and enhance food supply. PVC supported pit storage significantly reduced losses.